METAPHOR IN MODERN CHINESE SLANGS - Nga, Nguyen Thi (VNU Journal of Foreign Studies; Vol 37 No 2DO - 10.25073/2525-2445/vnufs.4709, 2021)
Metaphor is a rhetorical method used commonly in language in general and in slang in particular. With its iconic and implicit feature, metaphor makes language polished, refined and contains many layers of sophistication, beauty and sensuality. The paper examines The latest Chinese slang language by Li Shu My and Yan Li Gang and analyzes the basis and role of metaphor in modern Chinese slang.